2011
DOI: 10.1037/a0021110
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis generation, sparse categories, and the positive test strategy.

Abstract: If a paper is unpublished, the author may distribute it on the Internet or post it on a website but should label the paper with the date and with a statement that the paper has not (yet) been published. (Example: Draft version 1.3, 1/5/08. This paper has not been peer reviewed. Please do not copy or cite without author's permission.) Authors of articles published in APA journals may post a copy of the final manuscript, as accepted for publication, as a word processing file, on their personal website, their emp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 112 publications
4
95
1
Order By: Relevance
“…Thus, uncertainty sampling may be a general-purpose strategy that is less demanding but often consistent with normative principles. A similar point has been made in recent analyses showing that positive testing can be equivalent to information gain under certain conditions (Austerweil & Griffiths, 2011;Klayman & Ha, 1987;Navarro & Perfors, 2011). For example, Austerweil and Griffiths (2011) showed that when hypotheses make deterministic predictions about the next event in a sequence, testing the prediction of the most probable hypothesis (e.g., asking "is the next event A?"…”
Section: Relation To Other Modeling Approachesmentioning
confidence: 80%
See 1 more Smart Citation
“…Thus, uncertainty sampling may be a general-purpose strategy that is less demanding but often consistent with normative principles. A similar point has been made in recent analyses showing that positive testing can be equivalent to information gain under certain conditions (Austerweil & Griffiths, 2011;Klayman & Ha, 1987;Navarro & Perfors, 2011). For example, Austerweil and Griffiths (2011) showed that when hypotheses make deterministic predictions about the next event in a sequence, testing the prediction of the most probable hypothesis (e.g., asking "is the next event A?"…”
Section: Relation To Other Modeling Approachesmentioning
confidence: 80%
“…For example, for certain kinds of hypothesis spaces, confirmatory sampling is consistent with normative goals, precluding the need to consider more than one alternative (Austerweil & Griffiths, 2011;Klayman & Ha, 1987;Navarro & Perfors, 2011;Nelson & Movellan, 2001). Learners who correctly account for these constraints might be expected to show more or less confirmatory sampling depending on the problem space.…”
Section: An Intermediate Positionmentioning
confidence: 99%
“…A diagnostic test would be one in which the likelihood of a positive result differs between competing hypotheses (e.g., an elevated white-blood-cell count might be highly likely for appendicitis, but relatively unlikely for cracked ribs), providing the potential for revising beliefs about relevant hypotheses. Although some recent work has argued that confirmation testing can be a reasonable strategy once the complexity of realworld domains is accounted for Navarro & Perfors, 2011), diagnostic search has been observed under conditions that facilitate the consideration of alternatives (Mynatt, Doherty, & Dragan, 1993).…”
Section: Hypothesis Generation Influences Hypothesis-testing Behaviormentioning
confidence: 99%
“…Thus, the choice of an effective testing strategy in a situation is a question of ecological rationality in that it depends to a large degree on the structure of the environment Gigerenzer, Todd, & the ABC Research Group, 1999). Past work has shown that people behave in an ecologically rational fashion when sparsity is varied in a number of non-causal hypothesis testing tasks (where sparsity CAUSAL EXPERIMENTATION 8 applied to hypotheses or events, e.g., McKenzie, Chase, Todd, & Gigerenzer, 2012; Hendrickson, Navarro, & Perfors, 2016;Oaksford & Chater, 1994;Langsford, Hendrickson, Perfors, & Navarro, 2014;Navarro & Perfors, 2011). For example, Hendrickson et al (2016) showed that people switch from requesting positive to negative examples of a concept when the overall proportion of positive cases increases.…”
Section: Sparsity Determines Effectiveness Of Learning Strategiesmentioning
confidence: 99%
“…Here, too, the optimal strategy (in terms of expected information gain, see next section) is to ask questions targeting features that apply to half the possibilities under consideration (e.g., "Is the person female? ", if the hypotheses are people and half are each sex), because it reduces the number of alternatives more rapidly than asking about specific identities directly (e.g., Navarro & Perfors, 2011;Mosher & Hornsby, 1966).In analogy to the switch testing example presented above, inquiring about a feature means asking if any of the individuals sharing that feature is the target, just as turning on multiple switches asks if any of those switches has an effect on the outcome (the fan). An alternative approach to asking about shared features would be to test each person individually (e.g., "Is it Bob?").…”
mentioning
confidence: 99%